Geophysical methods for the investigation of a closed dumping ground - Chia, Charles Y. H. (2015)
Reclamation of closed dumping grounds is a potential solution to solve land scarce problems. Traditional geotechnical investigations of closed dumping grounds face some problems, such as the emission of hazardous liquids and gases, and the lack of ground information due to the discontinuity between two boreholes. Thus, noninvasive and continuous investigation methods are needed to supplement traditional geotechnical investigations. In this paper, two types of geophysical investigation methods, Seismic Analysis of Surface Waves (SASW) and 2D Resistivity, were carried out to study noninvasive and continuous site investigations for dumping grounds. The two geophysical methods are able to profile the distribution of physical properties of the fill and original materials, by which the extent of the dumping ground can be found and some anomalies in the subsurface can be located. Boreholes were used to assist in locating the dumping material-ground interfaces. The results show that dumping material-ground interfaces obtained from the two geophysical methods are roughly consistent. Moreover, attempt is made in the paper to use the geophysical methods to classify the types of dumping materials. The results show that the classification of dumping materials using the geophysical methods follows the results of the manual sorting of the dumping materials from a borehole.